PROGRAM WISATA BERSIH MELALUI PEMBERIAN REWARD DALAM MENINGKATKAN DAYA TARIK WISATAWAN DI BANYUWANGI - Nadiya Lifa Ningrum; Saiful Rohman (Jurnal Bisnis Terapan, 2020)
Tourism is the leading sector in Banyuwangi, but the increasing number of tourists who is visiting Banyuwangi will causes more and more volumes of waste. Bangsring Underwater is a top destination Banyuwangi that is Frequently visited by tourists. The purpose of this study is to find outthe solutionswhich related to waste problems in order to Minimized the impact and supporting factors and obstacles in the implementation of waste management programs in Bangsring Underwater tourism.The method in this study was qualitative method. The result of this study is lean tourism programs that Is realized by the movement for not leaving garbage on tourism place. This program is carried out by providing garbage bags from totebags as trash that cangenerated from every tourist activity during their visit. Garbage in the totebag is obtained from the packaging of food and beverage waste carried by tourists when traveling and garbage around them. When tourists left,. The totebag which is containing garbage must be returned to manager at the exit door. If they do that kind of thing, they will be rewarded This is an advantage in the program carried out by researchers. Reward in the clean travel program is an award for who has been following the rules which determined by tourism manager. The supporting factors in this program are come form management of bangsring underwater banyuwangi also departement of culture and tourism and the banyuwangi environment agency. While the inhibition is on formation of a hygiene monitoring team in Bangsring Underwater.